EGCG Mitigates Apoptosis of Lens Epithelial Cells in Age-Related Cataract via the PAK1/Cleaved Caspase-3 Pathway - Zhang, Yue; Su, Dongmei; Sun, Zhaoyi; Fu, Yanjiang; Chen, Xiaoya; Hu, Yuzhu; Zhang, Xiao; Zheng, Shunfei; Ma, Xu; Hu, Shanshan (Current Molecular Medicine, 2025)
BackgroundOxidative damage and apoptosis of lens epithelial cells (LECs) are the primary factors contributing to the development of age-related cataracts (ARC). The potential protective effects of epigallocatechin gallate (EGCG) on LECs remain unclear despite its remarkable antioxidant and anti-apoptotic properties. The aim of this study was to explore the role of serine/threonine-protein kinase (PAK1) in EGCG-mediated attenuation of H2O2-induced apoptosis of LECs in vivo and in vitro.MethodsPAK1 expression was assessed in the anterior capsule of the lens from mice and patients with and without ARC using western blotting and immuno-histochemistry. Human lens epithelial B3 (HLE-B3) cells were pre-treated with EGCG+H2O2 or H2O2 only, and PAK1 expression was determined using qRT-PCR and western blotting. Apoptosis (following PAK1 overexpression or silencing) and cell survival were assessed using Hoechst 33342 staining and a cell counting Kit-8 assay, respectively. Cleaved caspase-3 was measured in transected cells, aged/young mice, and mice treated with EGCG via western blotting.ResultsPAK1 expression was significantly lower in ARC LECs than in control LECs. In HLE-B3 cells, EGCG+H2O2 treatment upregulated PAK1 mRNA and protein expression when compared with H2O2 alone. PAK1 overexpression alleviated H2O2-induced apoptosis in LECs, while low expression weakened EGCG’s protective effects. PAK1 overexpression reduced cleaved caspase-3 expression in H2O2-treated cells, whereas PAK1 silencing increased its expression in EGCG+H2O2-treated cells. EGCG decreased cleaved caspase-3 expression in H2O2-treated cells. These results suggest that PAK1 inhibits cleaved caspase-3 expression, thereby enhancing EGCG’s attenuation of H2O2-induced LEC apoptosis.ConclusionThe PAK1/cleaved caspase-3 pathway plays a key role in EGCG’s protective effects on the development of ARC. This provides a new therapeutic target for the use of EGCG in preventing and treating ARC.
Keywords: apoptosis